RSV infection in Istanbul: risk factors and frequency: RSV infection - İzci Güllü, Elif; Akın, Yasemin; Karaaslan, Ayşe; Vayvada, Elif Ruşen; Atabek, Ayşe Ayzıt; Kaya Narter, Fatma (The Journal of Infection in Developing Countries, 2017)
Introduction: Respiratory syncytial virus (RSV) is one of the most common causes of acute respiratory infections in all age groups especially under two years. The aim of this study was to investigate the frequency and clinical features of RSV in hospitalized children under two years of age with the diagnosis of lower respiratory tract infections (LRTI) in our region. Methodology: Between September 2011- May 2013, hospitalized children aged 0-2 years with the diagnosis of viral LRTI, in which nasopharengeal secretions were tested for the presence of the RSV antigen, were included in this prospective study. Results: Among the total of 361 hospitalized children who were investigated for RSV antigen, 138 (38%) were female and 223 (62%) were male. The mean age of the group was 5,7±5,1 months (0-24 months). RSV antigen in nasopharyngeal secretions was positive in 68 (19%) of 361 patients. RSV infection was detected significantly higher in December and January (p = 0.003). RSV positivity was significantly higher in patients aged under 6 months (p=0.01), with shorter duration of breastfeeding (p = 0.02), low socioeconomic status (p = 0.02), and also born with spontaneous vaginal delivery (p = 0.007). In RSV(+) LRTI group, children were associated with severe disease than RSV (- LRTI group (p = 0.014). Conclusions: Since there is lack of data investigating the frequency and the risk factors of RSV respiratory infections in our region, the present study is important for providing new data. Furthermore, this is the second study investigating the correlation between RSV positivity and meteorological conditions in Turkey.